Colleges and schools-Craig School of Business-Entrepreneurship-0013
Ceronolta Raines, Mentor uses Windows 95 with Selma High School Students on their Theme folios home entertainment project. ( The Students) Left to Right Chyrl Ortega, Melissa Campos, Natalie Conde, Augstine Rayas.